Peso ideal de abate de tourinhos Jersey para produção de carne - Stanqueviski, Fernanda (2019)
With the growth of dairy farming in Brazil the chances of the use of the males for meat production increase. Thus, the objective of this work was to evaluate the best slaughter weight of Jersey bulls, aiming at the optimization of the use of these whole animals for meat production, evaluating the performance characteristics of the animals, carcass characteristics and slaughtered meat. The experimental design was a completely randomized design with three slaughter weights (360, 390 and 420 kg), with six replicates. The experiment was conducted at the Agronomic Institute of Paraná (IAPAR) of Pato Branco from May 2017 to September 2018. Eighteen newborns of the Jersey breed were used. The animals were submitted to a single lactation system, which consisted of four liters of milk, supplied twice a day for 51 days. The diet provided after breastfeeding consisted of 15% of oat hay, 68% whole corn grain and 17% soybean meal. There was a period of adaptation to the facilities and the management system employed, with duration of 15 days. The animals were weighed at the beginning and end of the experimental period, as well as every 28 days, for monitoring the ponderal development. After slaughter the animals were submitted to carcass evaluations. Absolute dry matter intake (CMS), mean daily weight gain (GMD) and feed conversion were not affected by the slaughter weight of the animals (P> 0.05). The thickness of the subcutaneous fat decreased from the animals slaughtered with 392 to those of 422 kg, causing the animals to present less requirement for gain, compensating the fall of the dry matter consumption relative to 100 kg of live weight. The warm carcass weight and cold carcass weight increased linearly with the increase in slaughter weight of the animals.